Putting Proverbs to the Test: An Engaging Approach for Developing Students' Hypothesis Testing Skills. (July 2019) - Gamble, Tim; Turner-Cobb, Julie M.; Walker, Ian; Holt, Nigel
Integral to most undergraduate psychology degree programs are research methods courses. Students learn about theory, study design and hypothesis testing, and gain knowledge that is assessed by laboratory reports. We describe a problem-based learning approach with an emphasis on acquisition of study design skills. Working in small groups, students took well-known falsifiable proverbs, developed hypotheses to test them, recruited and assessed participants, analyzed the data, and presented their findings in a poster format. This approach allowed students to develop key skills to systematically experiment with an idea using proverbs as a proxy for theory. We suggest proverb testing as a useful technique to engage student-centered active learning in psychology and in the behavioral sciences more broadly.